ETIKA BIROKRASI SEBAGAI FONDASI PENINGKATAN KUALITAS PELAYANAN PUBLIK DI INDONESIA - Dimas Anditiana Rachman; Ali Rokhman (Jurnal Progress Administrasi Publik, 2026)
This study aims to examine the relationship between bureaucratic ethics and the quality of public services in Indonesia. The main issue addressed is the weak internalization of ethical values such as integrity, accountability, professionalism, and fairness in the behavior of public officials, which has contributed to low public trust in the bureaucracy. This study employs a Systematic Literature Review (SLR) method by analyzing 17 scientific articles published between 2016 and 2024. Data were collected through searches in academic databases, including Google Scholar and Garuda, using the keywords “public service” and “bureaucratic ethics.” The results indicate that the low quality of public services is associated with weak bureaucratic ethics, as reflected in slow service delivery, lack of empathy, limited transparency, and inadequate service facilities. The study concludes that the implementation of bureaucratic ethical values plays a significant role in supporting the quality of public services in Indonesia. Keywords : Public Services; Bureaucratic Ethics; Quality of service; Systematic Literature Review